(untitled) (Ocean and Coastal Research, 2022)
The Santa Catarina Island Bay (SCIB) contributes with the largest production of cultivated oysters in Brazil, which is almost entirely based on hatchery produced cultchless oyster spat, whose metamorphosis is induced by an epinephrine solution. A production scale experiment was carried out to analyze the technical feasibility of the spat-on-shell system in SCIB. The experiment was carried out for 47 weeks, involving an internal phase, the larval settlement, and an external phase, encompassing nursery and growth. Nursery periods varied according to the experimental treatments: T3W - 3 weeks; T5W - 5 weeks; and T12W - 12 weeks. T3W and T5W showed lower survival during the two-week period shortly after transfer of the cultch from the nursery to the grow-out phase, likely linked to premature exposure of the spat in the cultch strings to predators such as fish. The 12-week nursery period showed the best results with clusters with a median of 6 animals and 11.4 g of meat per oyster at the end of the experimental period. Future studies could verify whether longer nursery periods or alternative methods to avoid exposure to predators can outperform these results.